Perencanaan Pemasaran dan Manajemen Risiko Bisnis Pengolahan Garam Industri Berkualitas dengan Berbasis Implementasi Teknologi - Nadia Widni Putri; Tantri Yanuar Rahmat Syah; Dimas Angga Negoro; Endang Ruswanti (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
PT Ladang Garam Nasional (PT LGN) aims to be a pioneer in the caustic soda salt industry in Indonesia by utilizing modern technology to meet the needs of the national chemical industry. This project is driven by Indonesia's dependence on industrial salt imports, especially for the chemical sector, which reaches more than 3 million tons per year. With the establishment of a factory in Tegal, Central Java, PT LGN will produce high-quality salt with a NaCl content of ≥99% through Fluidized Bed Dryer (FBD) technology and apply the principles of Good Manufacturing Practice (GMP). The global industrial salt market is projected to grow by 2.4% per year. PT LGN takes advantage of this opportunity by offering products that meet the specific needs of the caustic soda industry. The results of the study show that the adoption of technology in the production and distribution process can increase the added value of products and reduce operational risks significantly. Marketing strategies that focus on product diversification and market penetration have also proven effective in expanding consumer reach. This study contributes to the development of a sustainable business model in the industrial salt processing sector.